Export channel pricing management for integrated solutions - Henna Roine; Liisa-Maija Sainio; Sami Saarenketo (jbm - Journal of Business Market Management, 2012)
This article studies systems integrators' export channel pricing management for integrated solutions. We find support from our empirical case study for the notion that a systems integrator's export channel pricing strategy is multidimensional and dependent on international pricing environment and partner characteristics and that export partnerships have unique implications on a systems integrator's pricing process. The results show that giving up pricing control in export channel context may be suitable if the partnership is strategic. The findings also suggest that customer value-based pricing strategies instead of traditional cost-plus pricing methods should be adopted towards both end customers and channel members.
urn:nbn:de:0114-jbm-v5i3.238
Keywords: 650; export channel pricing; partnerships; integrated solutions; Export; Vertriebsweg; Betriebliche Preispolitik; Leistungsbündel